Facilitating community-based biocultural stewardship into transformative change: an ethnobiological perspective - Yao Fu; Prateep Panyadee; Yinxian Shi; Yingfeng Bi; Xuefei Yang (Current Opinion in Environmental Sustainability, 2026)

Spring drought variability in Yunnan within Southwest China from 1580s to 2020s and its impacts on social unrest - Qian Li; Yinxian Shi; Zhenhua Li; Bin Liu; Hua Huang; Xuefei Yang; Jianchu Xu; Yingfeng Bi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Functional interaction between Bacillus velezensis D103 and maize reveals a microbial mechanism for drought stress mitigation via photosynthesis and sugar metabolism - Yating Zhang; Zhenqiang Feng; Yanling Guo; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Bo Zhang; FangFang Yu; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; et al. (Plant Science, 2026)

Bacillus velezensis D103 enhances maize drought tolerance via ROS-scavenging and phenylpropanoid pathway activation - Yating Zhang; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Fangfang Yu; Bo Zhang; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; Ning Zhang; Bingxue Li (Plant Cell Reports, 2026)

Large-scale interviews and plot-based data reveal declining yields of the prized matsutake mushrooms in the major producing areas of China - Yingfeng Bi; Bin Liu; Guangli Chen; Ti Bu; Pengwan Zhang; Qinghong Zhou; Liqin Mu; Yao Fu; Yinxian Shi; Xuefei Yang; Deli Zhai (Journal of Environmental Management, 2025)

Achieving sustainable and highly efficient wood bonding through synergistic plant root-driven penetration mode with a hyperactive interface - Xiaoqian Bi; Yuan Zhang; Ping Li; Yan Wang; Yiqiang Wu; Yingfeng Zuo (Chemical Engineering Journal, 2024)

Ring-widths of Abies at tree-line ecotone reveal three centuries of early winter season temperature changes in Yunnan, China - Yingfeng Bi; Whitney Cory; Zenxin Fan; Jingchao Yang; Zhikun Wu; Wei Huang; Jianwen Li; Xuefei Yang (Climate Dynamics, 2020)
Variation in winter temperature is less well understood than in annual and summer temperatures over long timescales, particularly in low-latitude (0–30° N) montane regions with large spatial and topographic heterogeneity. Understanding these variations could be critical for forest manageemnt in these important tree growing regions. We collected tree-ring cores from Yunnan Province in montane southwest China, to determine how winter temperature has varied in the past and to explore its possible drivers in this region. Six highly correlated site chronologies were combined into a long and well-replicated regional composite (RC) chronology. The RC chronology correlated strongest with mean early winter season temperature (EWST) from November to January during 1959–2015. We applied RC chronology to reconstruct EWST from 1653 to 2015. The reconstruction shows five relatively warm historic intervals (1658–1718, 1743–1755, 1771–1791, 1929–1959, and 1995–2015) and cold intervals (1720–1742, 1792–1852, 1860–1883, 1905–1928, and 1960–1994). The 1950s with six anomalous warm seasons and 1980s with five anomalous cold seasons were the warmest and coldest decades, respectively. The EWST reconstruction generally agreed with other winter temperature reconstructions from nearby areas and with historical documents. Atlantic Multidecadal Oscillation (AMO) might be a key forcing of multidecadal winter temperature variations in montane southwest China over the past three and half centuries. Both warm and cold temperature periods coincide with respective positive and negative phases of AMO. Besides, the cold intervals during the nineteenth and twentieth centuries may also have been influenced by large volcano eruptions in low-latitude regions of south and east Asia. Our EWST reconstruction not only improves our understanding of the trends and variations of winter climate history, but also supports planning for resilience in conservation, agriculture, and forestry management in montane southwest China into the future.

Ring-widths of the above tree-line shrub Rhododendron reveal the change of minimum winter temperature over the past 211 years in Southwestern China - Yingfeng Bi; Jianchu Xu; Jinchao Yang; Zongshan Li; Aster Gebrekirstos; Eryuan Liang; Shibao Zhang; Yang Yang; Yongping Yang; Xuefei Yang (Climate Dynamics, 2017)

Assessing drought variability since 1650 AD from tree‐rings on the Jade Dragon Snow Mountain, southwest China - Yingfeng Bi; Jianchu Xu; Aster Gebrekirstos; Liang Guo; Mingxu Zhao; Eryuan Liang; Xuefei Yang (International Journal of Climatology, 2015)
Southwest China has experienced significant drought during the past few years. To better understand the tendency of drought changes over time, this study applies dendroclimatological techniques to assess drought variations in Lijiang Prefecture, southwest China. So far, the longest chronology (387 years) of Picea likiangensis on the Jade Dragon Snow Mountain was constructed, and the relationships between the tree‐ring width and climate variables were analysed. The spring season Palmer Drought Severity Index ( PDSI ) was reconstructed based on a standard chronology. Tree‐ring width is positively related to precipitation and relative humidity from February to March and the PDSI from January to May. Conversely, tree‐ring width is also negatively related with mean temperature from January to May, suggesting that growth of P. likiangensis is affected both by temperature and precipitation. The reconstructed PDSI showed that the Jade Dragon Snow Mountain has experienced considerable variations in spring drought conditions during the past 361 years. Four distinct periods were recognized: (1) 1650–1730, a relatively humid period with an average PDSI value above zero; (2) 1730–1860, a period with greatly fluctuating PDSI and intermittent wet periods (1746–1755, 1782–1800, and 1820–1830) and several dry periods (1735–1745, 1756–1780, 1810–1820, and 1830–1860); (3) 1870–1945, a humid period, with the highest PDSI value during 1930–1945; and (4) 1945–2011, a period with decreasing humidity. The results are consistent with hydrological studies in nearby regions and related species, as well as historical records of natural disasters. The recently observed spring drought follows a trend of decreasing humidity over the past 60 years, suggesting that a sound strategy for management and land‐use planning is required to secure ecosystem and human well‐being.